Paper Visualisasi Data Pembelian Barang dan Jasa Pada PT. Transcoal Pacific Menggunakan Exploratory Data Analysis: Visualization of Goods and Services Purchase Data at PT. Transcoal Pacific Using Exploratory Data Analysis - Chandra Ganda Manuel Malau; Binti Sholihah; Agus Salim (Penerbitan Universitas Trisakti, 2023)
The comfort and safety of the ship's crew in carrying out the voyage relies on the goods facilities and ship maintenance in carrying out shipping operations. In this case PT. Transcoal Pacific as a company engaged in logistics delivery services monitors with vendors engaged in the supply of goods in providing services in the form of ship crews and ship crews. However, in the implementation of business processes, there is no visual data that can provide information for companies regarding the purchase of goods and comparisons from 2 other branches. In this study, the preprocessing stage was carried out to eliminate inaccurate parts of the dataset and tables to create data visualization. After that, Exploration Data Analysis was carried out to obtain graphs to strengthen the analysis carried out. The expected result of this research is to form a dashboard as a place to visually process information to make the right decisions to improve business performance more effectively.